Dosimetric evaluation of incorporating the revised V4.0 calibration protocol for breast intraoperative radiotherapy with the INTRABEAM system. Issue 2 (10th February 2020) - Shaikh, Mubin Y.; Burmeister, Jay; Scott, Robin; Kumaraswamy, Lalith K.; Nalichowski, Adrian; Joiner, Michael C.
Abstract: In breast‐targeted intraoperative radiotherapy (TARGIT) clinical trials (TARGIT‐B, TARGIT‐E, TARGIT‐US), a single fraction of radiation is delivered to the tumor bed during surgery with 1.5‐ to 5.0‐cm diameter spherical applicators and an INTRABEAM x‐ray source (XRS). This factory‐calibrated XRS is characterized by two depth‐dose curves (DDCs) named "TARGIT" and "V4.0." Presently, the TARGIT DDC is used to treat patients enrolled in clinical trials; however, the V4.0 DDC is shown to better represent the delivered dose. Therefore, we reevaluate the delivered prescriptions under the TARGIT protocols using the V4.0 DDC. A 20‐Gy dose was prescribed to the surface of the spherical applicator, and the TARGIT DDC was used to calculate the treatment time. For a constant treatment time, the V4.0 DDC was used to recalculate the dosimetry to evaluate differences in dose rate, dose, and equivalent dose in 2‐Gy fractions (EQD2) for an α/β = 3.5 Gy (endpoint of locoregional relapse). At the surface of the tumor bed (i.e., spherical applicator surface), the calculations using the V4.0 DDC predicted increased values for dose rate (43–16%), dose (28.6–23.2 Gy), and EQD2 (95–31%) for the 1.5‐ to 5.0‐cm diameter spherical applicator sizes, respectively. In general, dosimetric differences are greatest for the 1.5‐cm diameter spherical applicator. The results from this study can be interpreted as a reevaluation of dosimetry or the dangers of underdosage, which can occur if the V4.0 DDC is inadvertently used for TARGIT clinical trial patients. Because the INTRABEAM system is used in TARGIT clinical trials, accurate knowledge about absorbed dose is essential for making meaningful comparisons between radiation treatment modalities, and reproducible treatment delivery is imperative. The results of this study shed light on these concerns.